1985
DOI: 10.1128/jcm.22.5.748-753.1985
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the detection of herpes simplex virus in direct clinical specimens with herpes simplex virus-specific DNA probes and monoclonal antibodies

Abstract: A comparison of two commercially available kits for rapid herpes simplex virus (HSV) detection directly in patient specimens was performed. The immunofluorescence assay (IFA) utilized monoclonal antibodies to HSV, and the DNA probe assay utilized three HSV sequences cloned into pBR322. A sample of 243 specimens received in viral transport medium were inoculated into MRC-5 tissue cultures. The remainder of the specimen was centrifuged, and the cellular pellet was examined by IFA and DNA probes. One hundred and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…Recently, there has been increasing interest in the application of ISH for HSV-infected specimens including genital and brain specimens because of the specificity and potentially high sensitivity of the technology. Forghami et al 15 reported 100% specificity and 94% sensitivity from herpetic encephalitis of frozen sections by ISH and Fung et al 16 also reported 74% sensitivity and 85% specificity in herpeticinfected specimens. Kobayashi et al 17 emphasized the usefulness of immunoperoxidase staining for the cytodiagnosis of herpetic infection compared with ISH.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been increasing interest in the application of ISH for HSV-infected specimens including genital and brain specimens because of the specificity and potentially high sensitivity of the technology. Forghami et al 15 reported 100% specificity and 94% sensitivity from herpetic encephalitis of frozen sections by ISH and Fung et al 16 also reported 74% sensitivity and 85% specificity in herpeticinfected specimens. Kobayashi et al 17 emphasized the usefulness of immunoperoxidase staining for the cytodiagnosis of herpetic infection compared with ISH.…”
Section: Discussionmentioning
confidence: 99%
“…Hybridisation is detectable by autoradiography. Spot hybridization or dot blotting as it is sometimes called has been used to detect many different viruses including herpesviruses (Fung, Shanley and Tilton 1985) and rotaviruses (Flores et al 1983) The polymerase chain reaction can synthesise millions of copies of a specific DNA sequence in a few hours. This procedure has been used in the identification of HIV in cells cultured from individuals suffering from AIDS (Kwok et al1987).…”
Section: Nucleic Acid Hybridisationmentioning
confidence: 99%
“…Other agents for which nucleic acid probes have been developed and analyzed include viruses such as CMV (30,100,150,158), HSV (34,52,91,149), human papillomavirus (179), adenovirus (60,174), hepatitis B virus (18), Epstein-Barr virus (24), and HIV (65). Nucleic acid probes for bacteria such as Salmonella typhi (145), legionellae (40), Vibrio cholerae (167), and campylobacters (167) also have been developed.…”
Section: Application Of Nucleic Acid Probesmentioning
confidence: 99%
“…2-acetylaminofluorene, use of polymeric alkaline phosphatase, and use of solution hybridization may improve the sensitivity of nucleic acid probes (52,93,106,175). In this regard, Gen-Probe (San Diego, Calif.) has incorporated solution hybridization into its nucleic acid probe assay.…”
Section: Application Of Nucleic Acid Probesmentioning
confidence: 99%